Relationship Between Feeding Pattern And Stunting In Toddlers In Panji Sibura Village , Sidikalang District 2021 - Wilda Yunita; Desi Handayani Lubis; Dwi Ris Hasanah S (Science Midwifery, 2022)
Stunting is one of the problems in the growth process because it is related to the problem of death, death, and brain development that is not optimal. Factors directly related to stunting are food intake and health status. Failure to thrive that occurs due to malnutrition at this time will have a bad impact on future life that is difficult to repair. The formulation of the problem is how the relationship between feeding patterns and the incidence of stunting in toddlers in Panji Sibura Village, Sidikalang District 2021. This type of research is analytical observational with a cross sectional design. The research is located in Panji Sibura Village, Sidikalang District. The research population is all mothers who have children under five with a total of 128. The sample size is 56 toddlers. Data analysis used univariate and bivariate with Chi Square test. The study found that there was a significant relationship between feeding patterns and the incidence of stunting. It is recommended for health workers to increase the stunting program that has been implemented.